Pola Konsumsi Protein Hewani Daging dan Telur Masyarakat Di Negeri Abubu Kecamatan Nusalaut Kabupaten Maluku Tengah - Mustafa, Jubeda; Liur, Isye J.; Jesajas, Heriyanus; Ririmase, Pieter M. (Universitas Pattimura, 2024)
This research aims to determine household consumption patterns of animal protein, meat and eggs in Nusa Laut District, Central Maluku Regency. The survey method was used in this research, where 30 household respondents were interviewed using a list of questions to obtain primary data. Secondary data was taken from the relevant agencies. Type of animal food, level of preference, method of obtaining it, reasons for consumption, frequency of consumption and amount of consumption are research variables. The research results show that the majority of households in the Nusa Laut District consume eggs compared to chicken and pork. This is because eggs are relatively cheaper and easier to obtain than chicken and pork.